Alternative Iran : contemporary art and critical spatial practice - Karimi, Z. Pamela (Zahra Pamela) (Stanford University Press, 2022)
""Alternative Iran" offers a unique contribution to the field of contemporary art, investigating how Iranian artists engage with space and site amid the pressures of the art market and the state's regulatory regimes. Since the 1980s, political, economic, and intellectual forces have driven Iran's creative class toward increasingly original forms of artmaking not meant for official venues. Instead, these art forms appear instead in private homes with "trusted" audiences, derelict buildings, leftover urban zones, and remote natural sites. These unusual cultural scenes are not only sites of personal encounters, but also part of the collective experience of Iran's citizens. Drawing on interviews with over a hundred artists, gallerists, theater experts, musicians, and designers, Pamela Karimi throws into sharp relief extraordinary art and performance activities that have received little attention outside Iran. Attending to nonconforming curatorial projects, independent guerrilla installations, escapist practices, and tacitly subversive performances, Karimi also discloses the push-and-pull games between the art community and the authorities, and discusses myriad instances of tentative coalition as opposed to outright partnership or uncompromising resistance. Illustrated with more than 120 full-color images, this book provides entry into Iran's unique artistic experiences without catering to voyeuristic curiosity around Iran's often-perceived "underground" culture"--